Notary's Responsibility for Legalizing Private Deeds in Foreign Languages - Utomo, Anggia Septiara Putri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The responsibility of notaries in the legalization of foreign-language private deeds is crucial in ensuring the validity and acceptance of documents in both domestic and international legal contexts. This study aims to analyze the role and responsibilities of notaries in the legalization process of private deeds written in a foreign language, as well as the challenges they face. The study explores how legalization affects the evidentiary value of the deed and the additional legal requirements that may be necessary for international recognition. Findings indicate that notarial responsibility includes thorough verification of translations and documents, as well as compliance with both domestic and international laws to ensure that documents are accepted in the destination country. The study concludes that best practices in legalization involve selecting qualified translators, meticulous documentation of the legalization process, and adherence to international legal requirements.